Universal Basic Income: Inspecting the Mechanisms - Nir Jaimovich; Itay Saporta-Eksten; Ofer Setty; Yaniv Yedid-Levi (Institute of Labor Economics (IZA), 2022)
We consider the aggregate and distributional impact of Universal Basic Income (UBI). We develop a model to study a wide range of UBI programs and financing schemes and to highlight the key mechanisms behind their impact. The most crucial channel is the rise in distortionary taxation (required to fund UBI) on labor force participation. Second in importance is the decline in self-insurance due to the insurance UBI provides, resulting in lower aggregate capital. Third, UBI creates a positive income effect lowering labor force participation. Alternative tax-transfer schemes mitigate the impact on labor force participation and the cost of UBI.
Keywords: E2; E6; J08; 330; universal basic income; labor force participation; inequality